THE USE OF AUDIO-VISUAL LEARNING MEDIA ON THE TRANSMISSION SYSTEM FOR STUDENTS IN CLASS XI LIGHT AUTOMOTIVE VEHICLE ENGINEERING 2 SMK NEGERI 1 PALANGKA RAYA OF THE ACADEMIC ON 2018/2019 - I Wayan Rismawan (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
The usage of Audio-Visual learning media is expected to help improving the students’ learning outcomes since it is been low category for while. The purpose of this method is to find out how the learning media such that can contribute in students’ learning result progress and how students can show the learning improvement as result of implementation of using Audio-Visual media. The descriptive method is applied for this research to describe the existing phenomena, in which based on current situation and past experience. We apply the quantitative research approach as the process of finding knowledge using data. This means that is as a tool to find information about as we desire to know. Furthermore, data collection techniques are based on the observation and test data sheet. Meanwhile, the observation aspects are designed as the activities of students and teachers in the learning process, and student responses in learning through Audio-Visual media model. The test problems utilize the multiple choice type with 5 alternative answer choices. By analysis of the observations of learning activities, it can be concluded that students provide the positive feedback to the learning model of Audio-Visual media. Based on the results of analysis of student’s academic record data, this learning media is able to give the effective method in improving the student learning outcomes. The academic record of students after implementing the Post-test shows that 96 % of students have reached the Minimum Completeness Criteria (MCC), which was about 70 % can get the achievement level of 80.12 %. If compared to the Pre-test results in previous section, there were around 25 students who did not pass the MCC score.